2016
DOI: 10.1515/amm-2016-0308
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Ho3+ in Static Magnetic Field

Abstract: The rare earths elements (REE) belong to the group of critical metals and they are achieving more and more interest due to their special properties. However, there occur some problems connected with their production. The most difficult phase is separation of REE. It includes a necessity to intensify currently applied processes and looking for new solutions. The present work introduces an idea to use differences in physical properties of the REE ions to get them separated. In the experimental part of the work s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 9 publications
(3 reference statements)
1
17
0
Order By: Relevance
“…where Abs λ is the absorbance value at a given λ wavelength [nm], ε λ is the molar absorption coefficient [dm 3 cm −1 mol −1 ], l is the optically active path length [cm] and C is a concentration of Ho(III) ions [moldm −3 ]. The values ε λ and l are constant and known [15] so it is possible to define the relationship between the concentration and absorbance as linear. The differences in the Ho(III) ions concentration from the two outputs were calculated as follows:…”
Section: Methods Of Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…where Abs λ is the absorbance value at a given λ wavelength [nm], ε λ is the molar absorption coefficient [dm 3 cm −1 mol −1 ], l is the optically active path length [cm] and C is a concentration of Ho(III) ions [moldm −3 ]. The values ε λ and l are constant and known [15] so it is possible to define the relationship between the concentration and absorbance as linear. The differences in the Ho(III) ions concentration from the two outputs were calculated as follows:…”
Section: Methods Of Analysismentioning
confidence: 99%
“…Among other things, the direct separation of ions allows solutions of certain metals to be concentrated with no need for nanoparticle synthesis or processes of adsorption and desorption on their surface which can make the processes last longer. Scientific works have dealt with the separation of ions of metals displaying ferromagnetic properties (Fe) [11] or ions of rareearth metals (REMs) [10,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 More recently, additional encouraging results on magnetomigration of ions have been published in the literature. 6- 12 Fujiwara et al demonstrated the separation of transition metals induced by magnetic field gradients of 40 mT 2 cm −1 . Silica gel supports were used to spot metal ions, which moved different distances depending on their magnetic susceptibilities.…”
mentioning
confidence: 99%
“…movement of paramagnetic ions of one type under the influence of a magnetic field, rather than magnetic separation. 14,15 Fujiwara et al demonstrated the motion of transition metal ions in solutions spotted on a silica gel support in the presence of magnetic fields. [16][17][18][19] Mach-Zehnder interferometry (MZI) was used to observe in situ the migration of Mn 2+ and Gd 3+ paramagnetic ions exposed to magnetic fields.…”
Section: Introductionmentioning
confidence: 99%